Social and economic decline as factors in conflict in the Caucasus - Svetlana P. Glinkina; Dorothy J. Rosenberg (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
We argue that the conflicts in the Caucasus are the result of the abrogation by the elite of the earlier, Soviet era, social contract. This process was accompanied by the collapse of the formal economy; evidenced by huge national income compression, falling public goods provision, and growing inequality and poverty. In the absence of state provision of basic amenities and governance, ordinary people are compelled to fall back on kinship ties. Declining standards of governance facilitate state-sponsored corruption and criminality in a setting where the shadow economic activity is increasingly important to individual survival strategies. Oil pipelines and the right to control the transit of goods both legal and illegal also underlie conflict in the region. Criminality has replaced ethnicity as the major motivation for conflict and conflict per se has become a lucrative source of income.
Keywords: O10; O53; P51; 330; Caucasus; conflict; natural resources; Sozialer Konflikt; Kriminalität; Kaukasus; Politischer Konflikt; Soziale Ungleichheit